# Cube of sum

Page navigation:

Definition.

The **сube of sum**of two expressions is equal to the сube of the first, plus three times the product of the square of the first and the second, plus three times the product of the first and the square of second, plus the сube of the second:

(a + b)^{3} = a^{3} + 3a^{2}b + 3ab^{2} + b^{3}

## Derivation of the formula of cube of sum

The proof of the formula is very simple. To prove the formula is sufficient to multiply the expression:

(a + b)

= (a + b)·(a

= a

= a

^{3}= (a + b)·(a + b)^{2}== (a + b)·(a

^{2}+ 2ab + b^{2}) == a

^{3}+ 2a^{2}b + ab^{2}+ ba^{2}+ 2b^{2}a + b^{3}== a

^{3}+ 3a^{2}b + 3ab^{2}+ b^{3}## Applying of cube of sum formula

Cube of sum formula convenient to use:

- to disclose the brackets
- to simplify expressions

## Examples of task

Example 1.

Expand brackets (x + 3)^{3}.

**Solution:** Apply the **cube of sum formula**.

(x + 3)

= x

^{3}= x^{3}+ 3·3·x^{2}+ 3·3^{2}·x + 3^{3}== x

^{3}+ 9x^{2}+ 27x + 27Example 2.

Expand brackets (2x + 3y^{2})

^{3}.

**Solution:** Apply the **cube of sum formula**.

(2x + 3y

= (2x)

= 8x

^{2})^{3}== (2x)

^{3}+ 3·(2x)^{2}·(3y^{2}) + 3·(2x)·(3y^{2})^{2}+ (3y^{2})^{3}== 8x

^{3}+ 36x^{2}y^{2}+ 54xy^{4}+ 27y^{6}Example 3.

Simplify the expression ^{3}+ 27x

^{2}+ 9x +1

^{2}+ 6x + 1

**Solution:** Apply the **cube of sum formula** in numerator and **square of the sum formula** in denominator.

^{3}+ 27x

^{2}+ 9x +1

^{2}+ 6x + 1

^{3}

^{2}

Factoring: Some special cases
Square of the sum
Square of the difference
Difference of squares
Cube of sum
Cube of difference
Sum of cubes
Difference of cubes

*Add the comment*